Evaluation of adsorptive characteristics of cow dung and rice husk ash for removal of aqueous glyphosate and aminomethylphoshonic acid - Garba, Jamilu; Abd. Wahid, Samsuri; Othman, Radziah; Ahmad Hamdani, Muhammad Saiful (Nature Publishing Group, 2019)
Glyphosate (GLY) is a major herbicide used throughout the world, and its continuous application has become an environmental issue. Adsorption is an important mechanism for removing organic contaminant in water. The present study characterized cow dung (CD) and rice husk ash (RHA), and determined the adsorption-desorption of GLY and its metabolite, aminomethylphoshonic acid (AMPA), on to them. The results revealed that both CD and RHA were alkaline and had no or low content of arsenic, cadmium, chromium and lead. The CD had lower surface area (13.104 mg2g−1) than RHA (21.500 m2g−1). The CD contained amines, phenol, ethers and carboxylic functional groups, while in addition to carboxylic and ether, RHA contains siloxane. Both CD and RHA had high affinities for GLY and AMPA. The Freundlich sorption coefficient (Kf) on AMPA were 2.915 and 2.660 for CD and RHA, respectively, while the values on GLY were 1.168 and 1.166 (mg g−1) for CD and RHA, respectively. Desorption of GLY only occurred at lower concentrations, while no desorption of AMPA was recorded, indicating their strong adsorption on CD and RHA. Considering their availabilities and affordable prices, both CD and RHA can be recommended as economical adsorbent for the removal of GLY and AMPA.